EKSISTENSI SANGGAR SENI PEDALANGAN NGESTI BUDHAYA KARANGANYAR DALAM PENGEMBANGAN SENI TRADISI - Jaka Rianto (Abdi Seni, 2016)
Indonesian Art Institute (ISI) Surakarta is one of the state educational institution of traditional art which have a mission in arts. The mission include both in art research and art producing/artworkthat is dedicated to human benefit. This art is always exist because it stands in an environment that support its existence. The community continually gives its contribution by giving a feed back. The development of art can be realized by the existence of arts creation intensly and supported by creative workers such as teachers, artists, critics, and art performers who have the ability to produce arts openly. There fore Indonesian Art Institute Surakarta as a barometer of art research and studies have an active role in holding a public service program for example in art studies. Art studies become supporting pillars of Javanese cultural art power this informal institution have big contribution in conservation, progress and the development of the Javanese arts. One of them isNgesthi Budaya studio. Ngesthi Budaya studio is located in Tegal Asri RT 04/07 Bejen, Karanganyar.This art studio is a target of training and constructing with the goal to make the pedalangan traditional art in progress and will not be extracted from its cultural root as a result of the influenceof global culture. The moral responsibility force the academics teachers of department pedalanganISI Surakarta to give more attention to this art studio. It is hoped that by the public service program can make Ngesthi Budaya art studio more exist, and transfers pedalangan art science academicly to the students. The form can be realized by training and constructing program about pedalangan elements to increase the students concept and skill in pedalangan field. This program may increasethe â€œNgesthi Budayaâ€ art studio existence in the society that may have attention from the young generation to respect, and love, and have some interest to conserve the traditional art heritaged from uor ancestors which contain high values.Key words :sanggar Ngesti Budhaya, art, shadow play.